Conducting Online Learning in Vocational School using Ms. Teams as A Learning Platform - Erna Wardani; Daffa Aditya Rusmanto; Slamet Riyadi (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
The background of this research was based on the global problem appeared in 2020-2021 namely Covid-19. It is a pandemic that forced classes to be conducted into online learning; however, the implementation of online learning remains as a great challenge for both teachers and students. They had to adapt with these new circumstances. Here, Ms. Teams was chosen by the school as their platform to conduct online learning. The foci of this research were to find out the students’ perception related to this application or platform called Ms. Teams and how it was implemented in the class. Descriptive qualitative research was employed and the data were obtained through questionnaire, interview and documentation. The results of questionnaire, the perception was positive with the detail; (1) Category 1 got score 95.4 with the index percentage 70%. (2) Category 2 got score 83 with the index percentage 61%. (3) Category 3 got score 77.6 with the index percentage 57%. The average percentage was 62% and it could be classified into Agree (Good). The conclusions were; (1) Ms. Teams is a good platform to conduct the online learning because this platform provide some exclusive features that make this platform special. (2) the implementation of online learning using Ms. Teams is good enough but there are several things needed as improvements.